History workshop : a journal of socialist historians. (Oxford : History Workshop Journal ; London : Distributed by Pluto Press, 1976)
"A journal of socialist and feminist historians."
Subtitle varies.
Has supplement: History workshop, a collectanea, 1967-1991.
Keywords: History -- Periodicals